Reducing Exhaust Emissions from Palm Oil Biodiesel Diesel Engines by Adding Hydrogen Gas - Kuntang Winangun; Yoyok Winardi; Indah Puspitasari; Nanang Suffiadi Akhmad; Riski Dwi Ardika; Salih Ozer (Automotive Experiences)
This study investigated the use of hydrogen enrichment with palm oil biodiesel in a compression ignition engine. The biodiesel was produced from crude palm oil (CPO) and injected into a single-cylinder diesel engine. Hydrogen gas was introduced into the intake manifold at varying flow rates 2.5 lpm, 5 lpm, 7.5 lpm, and 10 lpm. The engine used was a direct injection, single-cylinder diesel engine operating at a constant speed of 2000 rpm. The goal of the study was to evaluate the performance and emissions of the diesel engine running on CPO biodiesel fuel combined with hydrogen gas. Exhaust emissions and engine performance were investigated by examining smoke emissions, exhaust gas temperature, power, thermal efficiency, and fuel consumption. The addition of hydrogen showed improvements in performance and emissions. The best results occurred with the addition of 2.5 lpm hydrogen with optimal engine performance with an increase in BTE of 20.12%, while the decrease in fuel consumption was 27.57% compared to biodiesel. The addition of hydrogen gas has a positive impact on exhaust emissions (HC, CO2, and smoke opacity), but has a negative impact on NO emissions. At high loads of 2.5lpm hydrogen flow, emissions were obtained of 40.00ppm, 0.04%, 4.20%, and 44.20%, respectively, and an increase in NO emissions of 45.72%. Overall, the addition of hydrogen gas has a positive impact on the performance and exhaust emissions of biodiesel-fueled diesel engines.